2015
DOI: 10.1016/j.nicl.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted training modifies oscillatory brain activity in schizophrenia patients

Abstract: Effects of both domain-specific and broader cognitive remediation protocols have been reported for neural activity and overt performance in schizophrenia (SZ). Progress is limited by insufficient knowledge of relevant neural mechanisms. Addressing neuronal signal resolution in the auditory system as a mechanism contributing to cognitive function and dysfunction in schizophrenia, the present study compared effects of two neuroplasticity-based training protocols targeting auditory–verbal or facial affect discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
(97 reference statements)
4
24
0
Order By: Relevance
“…In line with previous studies, we showed that changes in EP observed in the SCTIG are likely driven by reorganization of brain areas necessary for perceptual analysis of faces in connection with areas implicated in the attribution of valance (Mazza et al, 2010; Popov et al, 2015; Campos et al, 2016). Using EEG, improvements in alpha power modulations have been observed in schizophrenia patients after training aimed at enhancing the analysis of perceptual features to promote social abilities (Popov et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies, we showed that changes in EP observed in the SCTIG are likely driven by reorganization of brain areas necessary for perceptual analysis of faces in connection with areas implicated in the attribution of valance (Mazza et al, 2010; Popov et al, 2015; Campos et al, 2016). Using EEG, improvements in alpha power modulations have been observed in schizophrenia patients after training aimed at enhancing the analysis of perceptual features to promote social abilities (Popov et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Using EEG, improvements in alpha power modulations have been observed in schizophrenia patients after training aimed at enhancing the analysis of perceptual features to promote social abilities (Popov et al, 2015). Mazza et al (2010) also found enhancement in emotional recognition of anger, disgust, and sadness through neuropsychological and physiological (i.e., N200) responses after an intervention relying on imitation theories (Mazza et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the degree of APS improvement occurring after one hour of exposure to auditory frequency discrimination training may indicate the degree to which adaptive tuning has taken place within temporal cortex; the positive association we observed between baseline verbal memory scores and APS improvement suggests that this tuning may be greater (or may occur more rapidly) in patients with relatively strong verbal memory abilities prior to training. Taken in context with previous research showing a positive relationship between APS improvements and cognitive enhancement (Fisher et al, 2015; Murthy et al, 2012; Popov et al, 2011; 2012; 2015), our results further suggest that patients with relatively intact verbal memory performance at baseline may ultimately be shown to respond better to ATCT than might patients with relative verbal memory impairments. This assertion makes intuitive sense, given that the learning and memory capabilities indexed by measures like the CVLT-II presumably engage similar neuroplastic mechanisms to those engaged by ATCT (e.g.…”
Section: 1 Discussionsupporting
confidence: 87%
“…Auditory perceptual improvements (i.e. auditory “tuning”) gained during treatment may be a key predictor of ATCT response, as they have been shown to correspond to overall degree of cognitive enhancement (Murthy et al, 2012; Popov et al, 2011; 2012; 2015). Notably, Fisher et al (2015) found that auditory processing speed improvements after 20 hours of training correlated with degree of cognitive enhancement after up to 40 hours of training, suggesting that these early auditory processing improvements may reflect the “plasticity potential” of the frontotemporal network and thus index the likelihood of cognitive benefit from ATCT.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Participants were recruited for a larger project on training-induced cortical reorganization in schizophrenia. Neuromagnetic indices and their association with cognitive tests for largely overlapping samples were reported before (Carolus et al, 2014) and after targeted, neuroplasticity-oriented intervention (Popov et al, 2015). The present results used entirely different scoring of the MEG data assessed prior to training.…”
Section: Participantsmentioning
confidence: 89%